Nutrition situation in Latin America and the Caribbean: current scenario, past trends, and data gaps - Luis Galicia; Rubén Grajeda; Daniel López de Romaña
ABSTRACT Objective To determine the current nutritional status in Latin America and the Caribbean (LAC) and identify data gaps and trends in nutrition surveillance. Methods A systematic Internet search was conducted to identify official sources that allowed for monitoring of LAC countries' nutritional status, including progress toward World Health Organization Global Nutrition Targets 2025. Reports from national nutrition surveillance systems and reports on nationally representative surveys were collected and collated to 1) analyze nutritional status, based on life-course anthropometric indicators and biomarkers, and 2) identify gaps in data availability and trends in nutritional deficiencies. Information on iron, vitamin A, iodine, folate, and vitamin B12 deficiency was also collected and collated. Results Twenty-two of the 46 LAC countries/territories (48%) had information on undernutrition (stunting, underweight, and wasting) in children under 5 years old and women of reproductive age (WRA). Seventeen countries (38%) had information on anemia in children under 5 years old and WRA, and 12 (27%) had information on anemia in pregnant women. Although overall nutritional status has improved in the past few decades in all countries in the region, some LAC countries still had a high prevalence of stunting and anemia in children and WRA. Overweight affected at least 50% of WRA in nine countries with available data, and was increasing in children. Data for school-age children, adolescents, adult males, and older adults were scarce in the region. Conclusions Overall nutritional status has improved in the LAC countries with available information, but more efforts are needed to scale up nutrition-sensitive and nutrition-specific interventions to tackle malnutrition in all its forms, as stunting, anemia, and vitamin A deficiency are still a public health problem in many countries, and overweight is an epidemic. Nutrition information systems are weak in the region, and countries need to strengthen their capacity to monitor nutritional status indicators.